Interpreting oblique impact data from an accelerometer-instrumented ice hockey helmet - Jorgensen, J. K.; Thoreson, A. R.; Stuart, M. B.; Loyd, A.; Smith, A. M.; Twardowski, C.; Gaz, D. V.; Hollman, J. H.; Krause, D. A.; An, K. A.; Stuart, M. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
The purpose of this study was to assess the correlations of acceleration measurements between an instrumented hockey helmet and the Hybrid III headform and to determine whether collision with a broad surface affects the correlations between these data. A CCM Vector hockey helmet, instrumented with the Head Impact Telemetry System, was fitted onto an instrumented Hybrid III headform and dropped onto an inclined plate to simulate impacts in hockey. The helmet and headform were dropped from 0.15, 0.30, and 0.60?m at different orientations to create impacts to the vertex, occipital, right, left, and forehead surfaces. Peak linear and rotational acceleration magnitudes and head injury criteria were assessed for each system. Correlations were assessed with the Pearson correlation coefficient, and linear regression models were generated. Relative error was assessed, and results were compared with the Wilcoxon signed rank test. Peak acceleration magnitudes generally had strong mathematical correlations, although a 1:1 linear relationship for rotational acceleration data was not observed. Differences between helmet and head peak acceleration magnitudes were significant. The linear relationship varied according to the impact direction. Instrumented helmet and head data demonstrated a strong mathematical correlation, but measures of linear acceleration generally had better 1:1 agreement than rotational acceleration measures. There is some dependence in the relationship between the helmet and head data on the impact direction, with vertex strikes showing the weakest correlation. Although data generated from the helmet may be useful for interpreting head accelerations experienced by on-ice players, additional analysis of the time-series data should be performed to understand its full utility.